Risk, Resources, and Education-Public Versus Private Financing of Higher Education. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper develops a public education scheme that takes uncertainty aspects of private educational investments explicitly into account. In the author's framework, the social merits of public education schemes are related to the lack of markets in which students can insure against educational risks. A case is made for tuition fees that depend on the expected returns of investments in education. The consideration of uncertainty provides a neglected link between educational choice, resource endowment, and productivity growth, which may serve to redefine the public role of education financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet